Going beyond ethnoracial discrimination and social support in accounting for psychological adjustment: Evidence for the importance of hope as a positive psychological construct in multiethnoracial adults. Issue 5 (3rd September 2019) - Chang, Edward C.; Chang, Olivia D.; Lee, Jerin; Lucas, Abigael G.; Li, Mingqi; Castro, K. Malulani; Pham, Savannah; Cho, Grace Y.; Purmasir, Yena S.; Yu, Elizabeth A.; Wu, Kaidi; Lui, P. Priscilla; et al.
ABSTRACT: In the present study, we examined the role of ethnoracial discrimination, social support (viz., family & friends), and hope (viz., agency & pathways) in accounting for negative psychological adjustment (viz., worry & depressive symptoms) and positive psychological adjustment (viz., vitality & life satisfaction) in a sample of 203 (164 females & 39 males) multiethnoracial adults. Results of conducting a series of hierarchical regression analyses indicated that beyond ethnoracial discrimination and social support, the inclusion of hope was found to augment the prediction model of psychological adjustment. Within the hope set, agency was found to be uniquely associated with adjustment. Pathways was found to be uniquely associated with positive indices of psychological adjustment. The present findings are the first to highlight the significance of hope in multiethnoracial adults. Some implications of the present findings for understanding psychological adjustment in multiethnoracial adults are discussed.